The effect of education using the emo-demo method on parents' knowledge and skills in preventing stunting - Maula Shofa; Mujito Mujito; Fiashriel Lundy (Universitas Ahmad Dahlan, 2024)
Stunting is a severe nutritional health problem in Indonesia, caused by an inadequate diet that interferes with a child's nutritional intake, resulting in significant impairment of growth and development. In Mangliawan Village, the prevalence of stunting is 3.8%, with 33 under-fives affected. Efforts to address this problem require effective interventions, one of which is through education aimed at parents. This study aims to analyze the effect of education using the emo-demo method on increasing parents' knowledge and skills in preventing stunting. The emo-demo method was chosen because of its participatory and interactive approach, making the material presented easier to remember and apply to participants. This study used a quantitative pre-experimental approach with a One Group Pretest Posttest design, involving 44 respondents selected by purposive sampling in Mangliawan Village during the period March-April 2024. Data were collected through a questionnaire consisting of 10 knowledge questions and 10 skill questions, then analyzed using the Wilcoxon Signed Rank Test. The statistical analysis showed a significant increase in parents' knowledge and skills after the education. The knowledge score improved with a Z value = -5.126 and P = 0.000, while the skill score also enhanced with a Z value = -5.400 and P = 0.000. These results show that the P value is <0.05, indicating a significant difference before and after the intervention. This finding confirms that the emo-demo education method effectively increases parents' understanding and ability to prevent stunting and is more impactful than other conventional education methods. This study is expected to be an effective alternative in public health education programs, especially in stunting prevention at the community level.